Breaking Connectivity Barriers: B-Smart as an Innovative Low-Bandwidth Mobile Learning Solution for Underserved Communities - Katemba, Petrus; Sumarlin, Sumarlin; Asmara, Jimi; Naatonis, Remerta Noni (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Access to digital learning resources remains a critical challenge in underserved communities, particularly those constrained by limited connectivity, inadequate infrastructure, and low-specification devices. This study aims to design, develop, and evaluate B-Smart, a low-bandwidth mobile learning application specifically engineered to bridge the digital learning gap in resource-limited educational environments. Methodology: A Design and Development Research (DDR) approach was employed, integrating an offline-first architecture, modular microlearning content, lightweight interface components, and data-efficient synchronization. Evaluation involved technical performance testing on low-end Android devices (1–2 GB RAM), usability testing using the System Usability Scale (SUS), pre-test and post-test learning assessments, and qualitative user feedback from 80 students and 15 teachers. Main Findings: B-Smart demonstrated reliable technical performance, with an average module loading time of 1.8 seconds, memory usage of 112 MB, weekly data consumption of 0.9–1.2 MB, and an offline access success rate of 98.7%. Usability evaluation yielded an SUS score of 82.4, while learning assessments revealed a mean post-test improvement of 24.6 points over pre-test scores, confirming significant knowledge gains across all user groups. Novelty/Originality of this study: These findings establish B-Smart as a novel, pedagogically sound, and technically efficient mobile learning solution tailored for low-bandwidth contexts. Unlike existing applications that depend on stable connectivity, B-Smart's offline-first, resource-efficient design ensures uninterrupted learning continuity in underserved regions. The study contributes a replicable development framework for scalable digital education initiatives, with practical implications for policymakers, educators, and developers seeking to advance equitable access to quality education in communities.